2013
DOI: 10.1002/hyp.9945
|View full text |Cite
|
Sign up to set email alerts
|

Combining two filter paper‐based analytical methods to monitor temporal variations in the geochemical properties of fluvial suspended particulate matter

Abstract: 9Many of the commonly used analytical techniques for assessing the properties of fluvial suspended 10 particulate matter (SPM) are neither cost-effective nor time-efficient, making them prohibitive to 11 long-term high-resolution monitoring. We present an in-depth methodology utilising two types of 12 spectroscopy which, when combined with automatic water samplers, can generate accurate, high-13 temporal resolution SPM geochemistry data, inexpensively and semi-destructively, directly from 14 sediment covered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Recently, studies have demonstrated the promise of spectral reflectance-based (visible and (near) infrared) fingerprinting methods as a quicker and less costly alternative for sediment source apportionment, with considerable potential to expand the temporal resolution of sediment fingerprinting analyses during high-flow events (e.g. Cooper et al, 2014aCooper et al, , 2014bEvrard et al, 2013;Martínez-Carreras et al, 2010;Poulenard et al, 2009;Tiecher et al, 2015).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Recently, studies have demonstrated the promise of spectral reflectance-based (visible and (near) infrared) fingerprinting methods as a quicker and less costly alternative for sediment source apportionment, with considerable potential to expand the temporal resolution of sediment fingerprinting analyses during high-flow events (e.g. Cooper et al, 2014aCooper et al, , 2014bEvrard et al, 2013;Martínez-Carreras et al, 2010;Poulenard et al, 2009;Tiecher et al, 2015).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…From each source area, 30 soil/sediment samples were collected, wet sieved to <63 μm to extract the fine clay‐silt fraction, and transferred onto quartz fibre filter papers. These filter papers were then analysed by X‐ray fluorescence spectroscopy to determine the geochemistry (wt.%) following the method of Cooper, Rawlins, Lézé, Krueger, and Hiscock (), which had previously been successfully applied in this catchment. In total, concentrations of eight major elements (Al, Ca, Ce, Fe, K, Mg, Na, and Ti) were determined and selected as fingerprints for use in the mixing models.…”
Section: Methodsmentioning
confidence: 99%
“…One litre grab samples were filtered through pre-weighed Millipore quartz fibre filter (QFF) papers with a particle retention rating of 99.3 % at 0.45 μm to extract SPM (Cooper et al 2014). Filters were then oven dried at 105°C for 2 h and reweighed to determine SPM concentration.…”
Section: Data Processingmentioning
confidence: 99%